Laju Pertumbuhan Luas Panen dan Produksi Padi di Provinsi Bengkulu Tahun 2019-2024 - Susila Isma; Shovia Alkesya Mardila; Tri Wahyuni Damayanti; Sazuli Sazuli; Reflis Reflis (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study aims to assess the growth rate of harvested area and rice production in Bengkulu Province during the 2019–2024 period and to examine spatial variation across districts as a basis for regional agricultural policy planning. The data used are secondary, consisting of a series of spatial and temporal data on harvested area and rice production; the analysis method includes calculating the compound annual growth rate (CAGR) for each indicator and examining temporal and spatial patterns across districts. The analysis results indicate a negative growth rate in the rice sector, with a relatively larger contraction in harvested area compared to production, accompanied by fluctuations and differences between years, indicating heterogeneity in agricultural performance at the district level. These findings have clear policy implications: the need for agricultural land protection measures, improvement and maintenance of irrigation infrastructure, increased farmer access to technology and markets, and the implementation of indicator-based growth rate monitoring to determine intervention priorities. To strengthen the policy base, recommended further research includes field verification and combined (quantitative-qualitative) studies to identify local factors driving the observed trends and fluctuations.